Dorsal oral mucosa graft urethroplasty for female urethral stricture reconstruction: A narrative review - Tao, Chunqin; Jin, Xiaoxiang; Zhang, Hengshu (Frontiers in Surgery, 2023)
Female urethral stricture is currently a challenging situation. In general, urethra dilatation can be selected for treatment, but the complications and high recurrence rate urge doctors to consider other treatments. Recently, dorsal oral mucosa graft urethroplasty is concerned by more and more surgeons, but there are not enough reports so far. A comprehensive search of dorsal oral mucosa graft urethroplasty was performed. According to the existing literature, there are applications of buccal mucosa and lingual mucosa, and compared with other kinds of grafts, the success rate is higher. However, there is a lack of multicenter, large sample and long follow-up studies. And there are still no enough comparative studies between different types of oral mucosa. In summary, dorsal oral mucosa graft urethroplasty is an effective option for the management of female urethral stricture. More multicenter and large sample studies with long-term follow-up data are needed.